2021
DOI: 10.1038/s41419-021-03853-y
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A2 deficiency promotes hepatocellular carcinoma progression by enhancing recruitment of myeloid-derived suppressors cells

Abstract: The main reason for poor prognosis in hepatocellular carcinoma (HCC) patients is high metastasis and recurrence. Cancer progression depends on a tumor-supportive microenvironment. Therefore, illustrating the mechanisms of tumor immunity in underlying HCC metastasis is essential. Here, we report a novel role of solute carrier family 7 member 2 (SLC7A2), a member of the solute carrier family, in HCC metastasis. The reduction of SLC7A2 was an independent and significant risk factor for the survival of HCC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…html) 65 , EZH2 (1/800, 0.53 μg ml −1 ; https://www.cellsignal.com/products/ primary-antibodies/ezh2-d2c9-xp-rabbit-mab/5246) 66 , LOX1 (1/800, 1.25 μg ml −1 ; https://www.merckmillipore.com/FR/fr/product/Anti-LOX-1-clone-9E12.1,MM_NF-MABS186), CD68 (1/1,000, 0.7 μg ml −1 ; https://www.abcam. com/cd68-antibody-epr20545-ab213363.html) 67 , CD11b (1/200, 0.5 μg ml −1 ; https://www.cellsignal.com/products/primary-antibodies/cd11b-itgam-d6 x1n-rabbit-mab/49420) 68 , CD14 (1/50, 0.07 μg ml −1 ; https://www.cellmarque. com/antibodies/CM/2066/CD14_EPR3653) 69 , CD15 (1/100, 5 μg ml −1 ; https:// www.bdbiosciences.com/en-us/search-results?searchKey=555400) 70 and S100A9 (1/16,666, 0.06 μg ml −1 ; https://cdn.origene.com/datasheet/um800066.pdf).…”
Section: Methodsmentioning
confidence: 99%
“…html) 65 , EZH2 (1/800, 0.53 μg ml −1 ; https://www.cellsignal.com/products/ primary-antibodies/ezh2-d2c9-xp-rabbit-mab/5246) 66 , LOX1 (1/800, 1.25 μg ml −1 ; https://www.merckmillipore.com/FR/fr/product/Anti-LOX-1-clone-9E12.1,MM_NF-MABS186), CD68 (1/1,000, 0.7 μg ml −1 ; https://www.abcam. com/cd68-antibody-epr20545-ab213363.html) 67 , CD11b (1/200, 0.5 μg ml −1 ; https://www.cellsignal.com/products/primary-antibodies/cd11b-itgam-d6 x1n-rabbit-mab/49420) 68 , CD14 (1/50, 0.07 μg ml −1 ; https://www.cellmarque. com/antibodies/CM/2066/CD14_EPR3653) 69 , CD15 (1/100, 5 μg ml −1 ; https:// www.bdbiosciences.com/en-us/search-results?searchKey=555400) 70 and S100A9 (1/16,666, 0.06 μg ml −1 ; https://cdn.origene.com/datasheet/um800066.pdf).…”
Section: Methodsmentioning
confidence: 99%
“…qPCR results showed that when ALKBH5 was knocked down, the mRNA levels of SLC7A2 and CGB3 were downregulated both in MGC-803 and HGC-27 cell lines, indicating that they are regulated by ALKBH5. While there was no distinct relation between these two genes and of GC, SLC7A2 has been proven to be lowly expressed in hepatocellular carcinoma (HCC) and suppress the progress of HCC (50). Furthermore, CGB3 also acts as a tumor suppressor in cervical cancer (51).…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A2, a member of the solute carrier family, was related to the amino acid transmembrane transporter activity. A latest research by Xia et al [23] , demonstrated that overexpression of SLC7A2 suppressed the invasion and metastasis of hepatocellular carcinoma by regulating myeloid-derived suppressors cell recruitment. However, increased ELMO2 [24] and TPM4 [25] were related to the proliferation and metastasis of different cancers respectively, suggesting that they might contributed little to the regulation of miR-451 on RF/6A cell proliferation.…”
Section: Discussionmentioning
confidence: 99%